2022
DOI: 10.1093/schbul/sbac030
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Machine Learning Algorithm for Structural Brain Images in Chronic Schizophrenia to Earlier Clinical Stages of Psychosis and Autism Spectrum Disorder: A Multiprotocol Imaging Dataset Study

Abstract: Background and Hypothesis Machine learning approaches using structural magnetic resonance imaging (MRI) can be informative for disease classification; however, their applicability to earlier clinical stages of psychosis and other disease spectra is unknown. We evaluated whether a model differentiating patients with chronic schizophrenia (ChSZ) from healthy controls (HCs) could be applied to earlier clinical stages such as first-episode psychosis (FEP), ultra-high risk for psychosis (UHR), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 66 publications
(83 reference statements)
0
6
0
Order By: Relevance
“…A lot of current machine learning based approaches distinguish patients with psychiatric disorders from healthy controls utilizing a single modality [5,6]. However, as multi-modality data is able to provide richer information, deep learning methods with multi-modality fusion is a promising direction to improve the model performance in a variety of medical image analysis tasks [7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…A lot of current machine learning based approaches distinguish patients with psychiatric disorders from healthy controls utilizing a single modality [5,6]. However, as multi-modality data is able to provide richer information, deep learning methods with multi-modality fusion is a promising direction to improve the model performance in a variety of medical image analysis tasks [7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…A biomarker of chronic schizophrenia may not predict conversion to psychosis in CHR cases, or response to a given treatment, or which circuits are the most amenable to neuromodulation. But the capacity of machine learning approaches to address these questions is developing, as predicting prognostic trajectories for high-risk or first-episode subjects is an active area of exploration [129][130][131] .…”
Section: Fmri Biomarkers Of Schizophreniamentioning
confidence: 99%
“…Structural MRI is gaining importance to help differentiate between SCZ and healthy controls, as summarized in de Filippis et al review [91•], as SVM could reach an accuracy of 100% if combined with more recent ML tools [92]. A parameter that has been studied as a potential biomarker of psychosis is the disrupted functional asymmetry: this value in the left thalamus discriminated control vs FEP/UHR individuals with high sensitivity (68.42% and 81.08% respectively) [93]. Antonucci et al found that SVM built with a repeated nested cross-validation framework was able to distinguish schizophrenia patients from HC by computing attentional control task in fMRI, to identify a pattern of connectivity alterations, with an accuracy of 66.9% [94].…”
Section: Neuroimagingmentioning
confidence: 99%